2017
DOI: 10.1108/edi-05-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Self-help groups: a seed for intrinsic empowerment of Indian rural women

Abstract: Purpose The purpose of this paper is to examine the role of self-help groups (SHGs) in providing an environment for the empowerment of Indian rural women. The authors argue that the SHG empowerment strategy paves the way for the process of development of bottom-up empowerment of women. The authors argue that SHG is a systematic strategy and is not solely based on credit, but also incorporates many other dimensions necessarily required for developing an empowerment process. Design/methodology/approach A quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
(19 reference statements)
4
25
0
3
Order By: Relevance
“…These results are consistent with previous research which showed that co-operatives in rural areas empower rural communities and women [1,4,5]. Co-operative members living in rural perceive co-operatives as providing more access to cooperative members to develop, obtain valuable information for businesses, get support, resources, formal and informal power.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with previous research which showed that co-operatives in rural areas empower rural communities and women [1,4,5]. Co-operative members living in rural perceive co-operatives as providing more access to cooperative members to develop, obtain valuable information for businesses, get support, resources, formal and informal power.…”
Section: Discussionsupporting
confidence: 92%
“…Different perceptions of rural and urban women regarding the structural empowerment of co-operatives also show that rural women have higher hopes for co-operatives compared to urban women, but this does not happen to men. Co-operatives become the main support to rural community economic development because co-operative has become a more easily accessible institutions for the rural communities when they want to get loans [1]. The conditions are flexible when compared to other conventional financial institutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations